(untitled) (Bangladesh Journal of Botany, 2025)
Eelgrass (Zostera marina L.) plays a vital role in coastal ecosystems, but its restoration is often hindered by low seed germination rates. This study was aimed to evaluate the effects of plant growth regulators (PGRs) on enhancing eelgrass seed germination under controlled conditions. Seeds were treated with different concentrations of GA3, 2,4-D and NAA. Results demonstrated that PGRs application significantly increased germination rates compared to control. These findings indicated that PGRs could be an effective tool for increasing the success of eelgrass restoration initiatives. Bangladesh J. Bot. 54(2): 389-392, 2025 (June)